Coal Demand, Market Forces, and US Coal Mine Closures - Brett Jordan; Ian A. Lange; Joshua Linn (Center for Economic Studies and ifo Institute (CESifo), 2018)
Economic transitions have the potential to displace workers and cause social unrest. Coal mine closures in the eastern United States due to the changing electricity system and the resulting employment losses in rural areas have become salient issues for all levels of government. Previous research has not distinguished among the potential causes of recent mine closures, such as rising production costs and decreasing coal demand from the electricity sector. This analysis utilizes unique data on coal mine and power plant operation to estimate the impact of supply and demand factors on mine closure. We model closure as a function of expected profits, which allows us to compare the effects on mine closure of specific demand and supply shocks to expected mine profits. Our results suggest that each shock substantially affected coal mine employment. Increasing costs of producing Appalachian coal have had the largest impact on closures with lower natural gas prices and lower electricity demand each accounting for a substantial number of closures additionally.
Keywords: L51; L71; Q35; Q53; 330; coal mining; firm exit; fuel procurement